Effective Principal Spiritual Leadership in Improving Teacher Motivation and Performance in Religious-Based Schools (Multi-Site Study of Muhammadiyah 7 Vocational High School Gondanglegi and Yos Sudarso Senior High School Batu) - Galuh Ratna Sumenggar; Ibrahim Bafadal; Juharyanto (al-Afkar, Journal For Islamic Studies, 2025)
Education plays a crucial role in instilling religious and national character values in line with the second principle of Pancasila: humanity that is just and civilized. Character education aims not only to transfer academic knowledge but also to shape students' attitudes and behaviors. However, phenomena such as violence, bullying, and brawls highlight a crisis in character that requires serious attention. Therefore, character education must be a priority and involve schools, parents, and the community. School leadership, particularly spiritual leadership, plays a strategic role in shaping students' character. Spiritual leadership involves applying spiritual values in decision-making and daily interactions, which can strengthen moral and ethical quality in schools. At SMK Muhammadiyah 7 Gondanglegi, spiritual activities like Morning Spiritual Greetings and group prayers help build character and discipline among students. At SMAK Yos Sudarso Batu, activities such as morning prayers and celebrating major Catholic holidays support students' spiritual development. This research explores how spiritual leadership at both schools motivates teachers and affects performance and character development. Using a qualitative approach with interviews, observations, and documentation studies involving principals, curriculum deputies, and teachers as participants, the research highlights the role of spiritual leadership in motivating and improving teacher performance. At SMAK Yos Sudarso, the new principal implements transformational leadership through open communication and regular training, creating a positive team dynamic. At SMK Muhammadiyah 7 Gondanglegi, despite leadership changes, the principal ensures that the school's vision is accepted through active communication and workshops, addressing challenges with support and recognition that motivate staff. Religious activities like morning prayers and celebrations strengthen spiritual commitment and work enthusiasm. Emotional support and altruistic culture improve teamwork and dedication. This research confirms that integrating spiritual values, effective communication, and emotional support is essential in creating a high-quality and productive work environment, enhancing staff motivation and performance, and supporting the school's vision and mission.